Penyuluhan Hukum Tentang Penyelesaian Sengketa Tanah Ulayat Melalui Jalur Non Litigasi Di Kampung Nolokla Distrik Sentani Timur Kabupaten Jayapura - James Yoseph Palenewen; Daniel Tanati; Yustus Pondayar; Frans Reumi; Eddy Pelupessy; Melkias Hetharia; Marthinus Solossa; Marthinus Mambaya; Farida Kaplele; Sara Ida Magdalena Awi; Karel V. H. Baransano; Margaretha G. M. I. Mamoribo; Dahliana Ketaren; Budiyanto; Dian Rahadian; Decky D. A. Wospakrik; Nur Asmarani; Hotlarisda Girsang; Thresia Hilda M. Y. Krey (AMMA : Jurnal Pengabdian Masyarakat, 2025)
This community service is carried out with the title Legal Counseling on the Settlement of Customary Land Disputes Through Non-Litigation Paths in Nolokla Village, East Sentani District, Jayapura Regency, this activity is carried out to partners due to cases from partners regarding misunderstanding regarding the settlement of customary land disputes based on applicable laws and regulations in order to obtain legal certainty and where the disputing parties do not want to give in or want to win alone so that with the expertise possessed by the servant can carry out legal counseling so that the disputing parties both win or win-win solution. The method of implementing this community service is carried out through lectures and discussions held on Saturday, May 31, 2025 which was held in Nolokla Village, East Sentani District, Jayapura Regency by providing knowledge to partners regarding the resolution of land disputes in general there are two types, namely dispute resolution through Litigation and Non-Litigation to obtain legal certainty, this activity begins with preparation and coordination, then presentation of material on how to resolve customary land disputes based on applicable laws and regulations. The output of this service is to provide partners with an understanding of how to resolve disputes through non-litigation channels along with the advantages and disadvantages of resolving such disputes and also provide legal assistance to partners to resolve cases related to customary land disputes.